Dengue NS1 antigen contributes to disease severity by inducing interleukin (IL)-10 by monocytes. (19th January 2016) - Adikari, T N; Gomes, L; Wickramasinghe, N; Salimi, M; Wijesiriwardana, N; Kamaladasa, A; Shyamali, N L A; Ogg, G S; Malavige, G N
Summary: Both dengue NS1 antigen and serum interleukin (IL)-10 levels have been shown to associate with severe clinical disease in acute dengue infection, and IL-10 has also been shown to suppress dengue-specific T cell responses. Therefore, we proceeded to investigate the mechanisms by which dengue NS1 contributes to disease pathogenesis and if it is associated with altered IL-10 production. Serum IL-10 and dengue NS1 antigen levels were assessed serially in 36 adult Sri Lankan individuals with acute dengue infection. We found that the serum IL-10 levels correlated positively with dengue NS1 antigen levels (Spearman's r = 0·47, P < 0·0001), and NS1 also correlated with annexin V expression by T cells in acute dengue (Spearman's r = 0·63, P = 0·001). However, NS1 levels did not associate with the functionality of T cell responses or with expression of co-stimulatory molecules. Therefore, we further assessed the effect of dengue NS1 on monocytes and T cells by co-culturing primary monocytes and peripheral blood mononuclear cells (PBMC), with varying concentrations of NS1 for up to 96 h. Monocytes co-cultured with NS1 produced high levels of IL-10, with the highest levels seen at 24 h, and then declined gradually. Therefore, our data show that dengue NS1 appears to contribute to pathogenesis of dengue infection by inducing IL-10 production by monocytes.